Herpes zoster in an 11‐month‐old immunocompetent infant: A rare case report. Issue 8 (30th April 2020) - Sah, Chandra Mohan; Shrestha, Sandeep; Chaudhary, Nagendra
Abstract: Herpes zoster generally occurs after the exposure of VZV following varicella. This case report emphasizes a rare case of HZ in an infant without prior history of varicella or its exposure in the baby, other siblings, and mother during or after the pregnancy. Abstract : Herpes zoster generally occurs after the exposure of VZV following varicella. This case report emphasizes a rare case of HZ in an infant without prior history of varicella or its exposure in the baby, other siblings, and mother during or after the pregnancy.